The welfare effects of time reallocation: evidence from daylight saving time. - Costa-Font, Joan; Fleche, Sarah; Pagán-Rodríguez, Ricardo Braulio (Wiley, 2024)
Daylight Saving Time (DST) is a widely adopted practice implemented by over 70 countries to align sunlight with day-to-day activities and reduce energy demands. However, we do not have a clear knowledge of how it affects individuals’ welfare. Using a regression discontinuity combined with a difference-in-differences design, we find that the Spring DST transition causes a significant decline in life satisfaction. By inducing a reallocation of time, the transition into DST deteriorates sleep quality and increases time stress, which in turn affects physical and emotional health. Using an event study approach, we find that such effects persist for about six days after the DST transition. Conversely, we provide evidence that the Autumn DST transition gives rise to a significant increase in life satisfaction. Finally, using a simple cost-benefit analysis, we discuss the potential benefits of ending DST.
Keywords: Jornada laboral - Efectos de la luz; Iluminación natural; Welfare effects; Time reallocation; Daylight saving time